System opieki nad małym dzieckiem w Danii z perspektywy osób rozważających emigrację - Kubiak , Hanna; Kubiak , Ewa (Studia Edukacyjne, 2024)
The purpose of this article is to present the Danish childcare system before starting school, to analyze the types of care available and its provision in the context of children’s developmental needs. The text describes types and terms of care and the care facilities. It also indicates the principles of the pedagogical plan, what values it reflects and what aspects of care and upbringing are paid attention to in Denmark. The system is described in the context of the assumptions of developmental psychology, and so the basis of the assumptions for caring for children and supporting their development is defi- ned. The developmental effects of implementing the pedagogical plan are analyzed.